Resourse Sharing in Technical Education Libraries:A Need - Palekar, B. R. (Journal of Engineering Education Transformations, 1989)
I n order to bring the various activities pertaining to Techhnical Education, at all levels under one roof, Department of Tech. Education’ was established in the Maharashtra state in the year 1948. This department controls Engg. colleges, Polytechnics, Technical Institutions, ITI’s Technical schools etc.